Re: ReplaceAll / sequential replacements versus joint replacement

*To*: mathgroup at smc.vnet.net*Subject*: [mg55448] Re: [mg55429] ReplaceAll / sequential replacements versus joint replacement*From*: Andrzej Kozlowski <akoz at mimuw.edu.pl>*Date*: Thu, 24 Mar 2005 03:41:48 -0500 (EST)*References*: <200503231034.FAA03987@smc.vnet.net>*Sender*: owner-wri-mathgroup at wolfram.com

On 23 Mar 2005, at 11:34, Ronald Wendner wrote: > Suppose there is an expression e1 which depends, among others, on > variables > a and b. > Replace both a and b by zero: > > e1/.{a->0,b->0} Mathematica gives, say, result1. > > Next, consider > > e2 = e1/.{a->0}; > e2/.{b->0} Mathematica gives, say, result2. > > How can result 1 differ from result 2? > > For my specific problem, I also attach a short Mathematica notebook. > [Contact the author to obtain the notebook - moderator] > > I'd appreciate any help. > > Many thanks, > Ron > > They certianly can differ, for example: (a - 2*b)/(a - b) /. {b -> 0, a -> 0} Indeterminate vs (a - 2*b)/(a - b) /. a -> 0 /. b -> 0 2 Andrzej Kozlowski Chiba, Japan http://www.akikoz.net/andrzej/index.html http://www.mimuw.edu.pl/~akoz/

**References**:**ReplaceAll / sequential replacements versus joint replacement***From:*"Ronald Wendner" <Ronald.Wendner@uni-graz.at>